The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2967/jnumed.107.039610
|View full text |Cite
|
Sign up to set email alerts
|

Use of 18F-FDG PET for Primary Treatment Strategy in Patients with Squamous Cell Carcinoma of the Oropharynx

Abstract: High tumor uptake of 18 F-FDG is associated with an unfavorable outcome in cancer patients. We evaluated pretreatment 18 F-FDG uptake as guidance for the primary treatment modality in patients with squamous cell carcinoma (SCC) of the oropharynx. Methods: Fifty-two consecutive patients with newly diagnosed resectable SCC of the oropharynx underwent 18 F-FDG PET before treatment. Primary treatment modalities consisted of surgical resection plus radiotherapy (RT) (surgery group, n 5 31) or radical RT plus chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…Previous studies on often nonuniformly treated cohorts of patients with head and neck cancer reported the prognostic potential for the more commonly used PET tracer 18 F-FDG (33)(34)(35). High pretreatment 18 F-FDG uptake was associated with poor outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on often nonuniformly treated cohorts of patients with head and neck cancer reported the prognostic potential for the more commonly used PET tracer 18 F-FDG (33)(34)(35). High pretreatment 18 F-FDG uptake was associated with poor outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that high glucose uptake or Glut-1 expression predicts poor prognosis and that Glut-1 levels often are elevated in 18F-FDG-avid tumors, [30][31][32][33][34][35][36][37][38][39][40][41] but their regional or microregional spatial association has seldom been studied and remains unclear. Our colocalization analysis of 18 F-FDG uptake and Glut-1 expression shows some, albeit weak, spatial linkage and again the strongest correlation was observed in the relatively nonglycolytic tumor model (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/ CT can improve risk prediction and shows prognostic value as a biomarker of HNSCC [14,15]. The maximum standardized uptake value (SUV max ), which is currently the most commonly used parameter in 18 F-FDG PET/CT [12,13,16], is an easily readable value that can be determined by estimating the highest intensity of 18 F-FDG uptake. However, it does not reflect the metabolic activity of the whole tumour [17].…”
Section: Introductionmentioning
confidence: 99%